2019
DOI: 10.1186/s13059-019-1697-0
|View full text |Cite
|
Sign up to set email alerts
|

WhoGEM: an admixture-based prediction machine accurately predicts quantitative functional traits in plants

Abstract: The explosive growth of genomic data provides an opportunity to make increased use of sequence variations for phenotype prediction. We have developed a prediction machine for quantitative phenotypes (WhoGEM) that overcomes some of the bottlenecks limiting the current methods. We demonstrated its performance by predicting quantitative disease resistance and quantitative functional traits in the wild model plant species, Medicago truncatula , using geographical locations as covariates for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 113 publications
2
13
0
Order By: Relevance
“…• C and 25/15 • C). Different letters indicate significant differences among year for each temperature (Fisher's LSD test, α = 0.05), Table S1: List of tested Medicago accessions with calculated seed dormancy traits and extracted environmental variables, Table S2: Basic descriptive statistics of 23 bioclimatic variables and 10 soil variables of sites of accessions origin, Table S3: Classification of 176 M. truncatula accessions in four cluster based on environmental and climatic conditions, Table S4: Pearson coefficients-probabilities between dormancy traits and bioclimatic variables, Table S5: Regression coefficient (r2) between environmental variables and plasticity index by macroecological and genetic clusters [106], Table S6: Complete list of QTN identified by GWA studies for each dormancy trait, Table S7: Over-representation analysis of the 136 candidate genes potentially involved in dormancy traits.…”
Section: Discussionmentioning
confidence: 99%
“…• C and 25/15 • C). Different letters indicate significant differences among year for each temperature (Fisher's LSD test, α = 0.05), Table S1: List of tested Medicago accessions with calculated seed dormancy traits and extracted environmental variables, Table S2: Basic descriptive statistics of 23 bioclimatic variables and 10 soil variables of sites of accessions origin, Table S3: Classification of 176 M. truncatula accessions in four cluster based on environmental and climatic conditions, Table S4: Pearson coefficients-probabilities between dormancy traits and bioclimatic variables, Table S5: Regression coefficient (r2) between environmental variables and plasticity index by macroecological and genetic clusters [106], Table S6: Complete list of QTN identified by GWA studies for each dormancy trait, Table S7: Over-representation analysis of the 136 candidate genes potentially involved in dormancy traits.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the genetic 5 3 0 groups identified by Gentzbittel et al (2019) to our study macroclimatic clusters and found 5 3 1 significant correspondence (r 2 =0.582**, Table S5). As discussed in Gentzbittel et al (2019),…”
Section: 8mentioning
confidence: 89%
“…Regression coefficient (r 2 ) between environmental variables and plasticity index by macroecological and genetic clusters ofGentzbittel et al (2019).…”
mentioning
confidence: 99%
“…While MAS/MABC has been successfully used for product development, HBB has shown huge potential for trait improvement in rice ( Abbai et al, 2019 ) and pigeonpea ( Sinha et al, 2020 ). During recent years the accuracy and prediction of predicting phenotypes in genomics selection has been improved extensively through approaches including (i) estimating global GEBVs while considering interaction of marker and environment covariates (G × E) ( Jarquín et al, 2014 ; Crossa et al, 2017 ), (ii) estimating haplotype/bin- based local GEBVs ( Voss-Fels et al, 2019 ), (iii) WhoGEM approach that explores the relationships between phenotypes and admixture components, land types, admixture components × environment interactions, and controls for the environment ( Gentzbittel et al, 2019 ), and (iv) optimal contribution selection method that enables simultaneous trait improvement and enriching the genetic base ( Woolliams et al, 2015 ; Cowling et al, 2017 ). In case, a causal gene is available for a trait, gene editing approach can be used for the trait improvement ( Zhang et al, 2018b ).…”
Section: Future Perspectivesmentioning
confidence: 99%